2011
DOI: 10.1093/nar/gkr031
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the varied glycosidic conformational, G-tract length and sequence preferences for anti-parallel G-quadruplexes

Abstract: Guanine-rich DNA sequences tend to form four-stranded G-quadruplex structures. Characteristic glycosidic conformational patterns along the G-strands, such as the 5′-syn-anti-syn-anti pattern observed with the Oxytricha nova telomeric G-quadruplexes, have been well documented. However, an explanation for these featured glycosidic patterns has not emerged. This work presents MD simulation and free energetic analyses for simplified two-quartet [d(GG)]4 models and suggests that the four base pair step patterns sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
238
5
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(265 citation statements)
references
References 90 publications
20
238
5
2
Order By: Relevance
“…We suggest that the specific ion binding to the narrow grooves may be another structural and free energy factor which contributes to the basic rules determining stabilities of different G-DNA topologies [22,29,30,63]. We plan to further investigate this issue in the near future.…”
Section: Cation Binding To Narrow Groove Leads To Increased Structuramentioning
confidence: 99%
See 2 more Smart Citations
“…We suggest that the specific ion binding to the narrow grooves may be another structural and free energy factor which contributes to the basic rules determining stabilities of different G-DNA topologies [22,29,30,63]. We plan to further investigate this issue in the near future.…”
Section: Cation Binding To Narrow Groove Leads To Increased Structuramentioning
confidence: 99%
“…Moreover, additional diversity is brought by syn or anti orientation of the glycosidic torsion angle c of guanosines in the G-stem. The possible syn/ anti patterns are constrained by strand orientations and affected also by presence or absence of flanking nucleotides at the beginning/end of a sequence [29,30]. Thus far, six distinct folding topologies of telomeric G-quadruplex were reported [12e16,27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The simple molecular mechanics force field is still almost universally used, with the formalism being that the energetics of a molecule (V) is described in terms of the sum of a number of factors: The AMBER force field has been extensively parameterized for nucleic acids (see Pérez et al, 2007 for a recent update of backbone parameters) and is the most commonly used one for quadruplex simulations, usually performed within the AMBER11 package (http://ambermd.org). Molecular dynamics simulations of a number of quadruplex systems have now been successfully performed and in large part they are able to reproduce experimental findings, not least the relative energetics of G-quartet base stacking in quadruplexes (see for a recent example, Cang, Šponer & Cheatham, 2011). Use of simulation methods for the modeling of quadruplex complexes involving new ligands is becoming an increasing popular approach to rational quadruplex ligand discovery; it is important to ensure that force-field parameters are not used that are inappropriate for nucleic acids.…”
Section: Modeling Of Quadruplex Structuresmentioning
confidence: 99%
“…In line with these differential thermal stabilities, molecular dynamics simulations and free energy analyses suggested that syn-anti and syn-syn are the most stable and most disfavored glycosidic conformational steps in antiparallel quadruplex structures, respectively. [13] It is therefore remarkable that an unusual all-syn G-tract forms in the thermodynamically most stable modified quadruplex, highlighting the contribution of connecting loops in determining the preferred conformation. Apparently, the particular loop regions in ODN(0) resist topological changes even upon enforcing syn$anti transitions.…”
mentioning
confidence: 99%